Impacts of feeding organic acid-based feed additives on diarrhea, performance, and fecal microbiome characteristics of pigs after weaning challenged with an enterotoxigenic strain of Escherichia coli. Issue 4 (10th November 2021) - Pluske, John R; Turpin, Diana L; Sahibzada, Shafi; Pineda, Lane; Han, Yanming; Collins, Alison
Abstract: Post weaning diarrhea (PWD) caused by enterotoxigenic strains of E. coli (ETEC) remains a major problem in the industry, causing decreases in performance and survival of weaned pigs. Traditionally, antimicrobials have been used for its mitigation/control. This study tested the hypothesis that a combination of two organic acid (OA)-based commercial feed additives, Presan FX [an OA, medium-chain fatty acid (MCFA) and phenolic compound-based product] and Fysal MP (free and buffered OA based on formic acid), would reduce PWD and improve post-weaning performance in pigs challenged with an F4-ETEC. This combination was assessed against a Negative control diet without any feed additives and a diet containing amoxicillin. Combined with a reduction in temperature during the infection period, inoculation with F4-ETEC resulted in 81% of pigs developing diarrhea, but with no differences between treatments ( P > 0.05). However, between days 14 to 20 of the study and due to colonization by Salmonella serovars, pigs fed the combination of Presan FX and Fysal MP showed less ( P = 0.014) diarrhea commensurate with a lower ( P = 0.018) proportion of Salmonella numbers relative to total bacterial numbers. This caused less ( P = 0.049) therapeutic antibiotic administrations relative to the diet with amoxicillin during this time. The diversity of bacteria within amoxicillin-treated pigs was lower ( P = 0.004) than the diversity in control or Presan FX + Fysal MP-treated pigs ( P = 0.01). Pair-wise comparisons showed that amoxicillin-treated pigs had altered ( P < 0.001) fecal microbial communities relative to both Presan FX + Fysal MP-treated pigs and control pigs. Amoxicillin-treated pigs were characterized by an increased abundance of bacterial families generally linked to inflammation and dysbiosis in the gastrointestinal tract (GIT), whereas Presan FX + Fysal MP-treated pigs had an increased abundance of bacterial families considered beneficial commensals for the GIT. Control pigs were characterized by an increased abundance of Spirochaetaceae associated with healthy piglets, as well as bacterial families associated with reduced feed intake and appetite. The combination of two OA-based feed additives did not reduce the incidence of F4 ETEC-associated diarrhea nor enhance performance. However, the combination markedly reduced diarrhea caused by Salmonella that occurred following the ETEC infection, commensurate with less therapeutic administrations relative to the diet with amoxicillin.